2015
DOI: 10.1007/s40519-015-0239-3
|View full text |Cite
|
Sign up to set email alerts
|

Body size perception and ideal body size in overweight and obese young adult women

Abstract: Purpose The purpose of this study was to examine the differences among actual body size, perceived body size and ideal body size in overweight and obese young adult women. Methods Actual body size was assessed by body mass index (BMI) while self-perceived and ideal body sizes were assessed by the Body Image Assessment Tool-Body Dimension (BIAS-BD). Descriptive statistics were calculated and analysis of variance (ANOVA) was performed on actual BMI as a function of perceived BMI. Results Of the 42 participan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 24 publications
2
12
0
Order By: Relevance
“…Findings from this research supported previous studies that found many women who have a healthy body weight perceived themselves as being overweight (Brener et al., ; Burke, Heiland, & Nadler, ; Lerner et al., ; Tiggemann, Winefield, Winefield, & Goldney, ). Many women with a healthy body weight overestimate their weight status due to strong social comparisons and a pervasive emphasis of the ideal female figure presented in the media (Cash, ; Steenhuis et al., ).…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…Findings from this research supported previous studies that found many women who have a healthy body weight perceived themselves as being overweight (Brener et al., ; Burke, Heiland, & Nadler, ; Lerner et al., ; Tiggemann, Winefield, Winefield, & Goldney, ). Many women with a healthy body weight overestimate their weight status due to strong social comparisons and a pervasive emphasis of the ideal female figure presented in the media (Cash, ; Steenhuis et al., ).…”
Section: Discussionsupporting
confidence: 88%
“…According to Lerner et al. (), body dissatisfaction and body size misperception are two factors that emerge and negatively affect body image. Body size misperception occurs when one is unable to correctly recognize his/her body size (Powell et al., ).…”
Section: Review Of Literaturementioning
confidence: 99%
See 2 more Smart Citations
“…Also, these persons may not clearly see the problems causing obesity because obesity may have a genetic connection (e.g., family) as well as a social connection where there are shared ideas about food, lifestyle, and/or values about body size (Christakis & Fowler, 2007). Because accurate body image improves adherence to obesity treatment regimens and the effect of weight loss programs (Dorsey, Eberhardt, & Ogden, 2009; Duncan et al, 2011), an intervention targeting overweight and obese emerging adults would benefit from using scripted information that reframes comments about body size to avoid being regarded as offensive while improving the accuracy of perceptions of their bodies (Lerner, Klapes, Mummert, & Cha, 2016)…”
Section: Discussionmentioning
confidence: 99%